(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Another important factor affecting decision-making related to determining the structure and content of the quality management system in educational institutions and its maintenance is the global nature of the problem and the general trends in the world in approaches to its solution. In this regard, this article discusses the development of the education quality management system in universities. The author analyzed the education system in a number of countries. A comparative review of the higher education evaluation system in different countries shows that there are different approaches to evaluating the activities of higher education institutions. The analysis of foreign experience made it possible to form a number of basic principles necessary for quality management in educational organizations.